Enhancing smart city mobility using Software Defined Networks - Ahmed, Zeinab E; Hassan Abdalla Hashim, Aisha; Saeed, Rashid A; Saeed, Mamoon M (IEEE, 2024)
Smart cities face challenges in mobility management, such as scalability, latency, resource allocation, security, and energy efficiency, which traditional methods struggle to address effectively. Software Defined Networking (SDN) is a rapidly evolving field that provides centralized control and programmability of network devices. SDN-based MM can advance sustainable urban development by centralizing control, adapting to changes, optimizing resource allocation, reducing energy consumption, and improving urban mobility. This paper investigates SDN's role in enhancing urban sustainability and analyzes its implications for sustainable cities. The paper categorizes the use of SDN technology to improve various aspects of smart cities into three categories: Emergency Services and Traffic Management, Security and DDoS Defense, and Network Performance. Results showed a 20% reduction in average travel times and a 33% improvement in emergency response times. Future research should focus on advanced real-time traffic management algorithms, integrating emerging technologies like 6G, and artificial intelligence to improve SDN-based systems' scalability and efficiency in smart cities.